Young farmers as innovation enablers in rural areas : the role of the EU’s support in a Portuguese peripheric region, Trás-os-Montes - Guerra, Ana Isabel (2019)
The European Union has suggested several approaches to decrease regional asymmetries and develop rural areas around member states. The main purpose of this paper is to study one of these policies, the Young Farmers Program, in a rural and peripheric region of Portugal, Trás-os-Montes. Since severe depopulation and ageing are some of this region’s biggest threats, initiatives like the Young Farmers Program might represent a gradual reversion of such phenomenon and contribute to the attractiveness of the rural lifestyle to the younger generations. But do these farmers truly bring innovation and modernization to Trás-os-Montes? Do they have a significant environmental and sustainability awareness? Is the digital usage already a reality? Are the associative leaders encouraging the sustainable development of the region? Is this new generation aware of the meaning and potentialities of the circular economy? Does it intend to adopt its innovative and modern practices? A tentative answer to these questions is searched by means of a detailed survey by questionnaire to a representative sample of young farmers in the region and by directly interviewing their main associative leaders.